Prevalence of High Risk Bacterial Pathogens in Indian Fresh Vegetables and Novel Strategies for Their Inactivation - Singla, Richu (My University, 2012)
A total two hundred and thirty six vegetable samples were collected from different locations of Patiala city mainly focusing on three main sites; farm, local distribution site and street vendors. Subsequent analysis for pathogens indicated Salmonella typhimurium, Shigella flexneri and Cronobacter sakazakii were isolated from the samples which were collected from street vendors respectively in Daucus carota (carrot), Brassica rapa (turnip), Raphanus sativa (radish sprouts), Phaseolus aureus (moong bean sprouts), Agaricus bisporous (button mushroom) and Piper betle (betel leaves). Organic acids (1.2%); malic acid, acetic acid, lactic acid and citric acid and ozone (1 ppm) was effective for the control of pathogens in broth. Salmonella typhimurium was resistant to high concentration of organic acids (2%). But, treatment on vegetable samples 2% of malic acid along with 2 ppm of ozone inhibited the growth of the pathogens to the acceptable levels. As a result, the combined treatment was significantly effective for the control of pathogens as described by Food and Drug Administration. It was observed that both the Salmonella isolates were able to form biofilms and their capacity to biofilm on polyethylene bags, PVC pipes and microtitre plates was tested. As a result, both the isolates were able to form biofilms. But, combined treatment of 2 ppm ozonated water and 2% of malic acid inhibited the biofilm formation in poly bags, PVC pipes, microtitre plates as well as in vegetable samples. No significant change in the essential nutritional parameters in terms of antioxidants, polyphenols, flavonoids, free radical scavenging activities as well as sensory properties of the treated vegetables was observed following sanitizer treatment. Although, reduction in microflora on whole and fresh-cut produce is dependent upon the type of produce and the type of natural microflora present, the proposed combined technology for inhibiting high risk pathogens may be applied to other fresh produce commodities ultimately increase the export options for India.
Keywords: Fresh Produce, Sanitizer, Food Borne Pathogens, Minimal Processing, Ozone, Organic Acid